2000
DOI: 10.1136/ewjm.172.5.315
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of questions asked by family physicians regarding patient care

Abstract: ⅷ Objectives To characterize the information needs of family physicians by collecting the questions they asked about patient care during consultations and to classify these in ways that would be useful to developers of knowledge bases. ⅷ Design An observational study in which investigators visited physicians for two half-days and collected their questions. Taxonomies were developed to characterize the clinical topic and generic type of information sought for each question. ⅷ Setting Eastern Iowa. ⅷ Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The success of such search engines to answer clinical questions is therefore limited. Indeed, Ely et al [8] concluded that clinicians usually do not spend more than two minutes to search for an answer to a clinical question before giving up.…”
Section: Introductionmentioning
confidence: 99%
“…The success of such search engines to answer clinical questions is therefore limited. Indeed, Ely et al [8] concluded that clinicians usually do not spend more than two minutes to search for an answer to a clinical question before giving up.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical questions have been categorized as to the kind of knowledge they sought and the kind of answers they needed, with taxonomic and other organizing structures proposed for them [ 24 , 27 , 35 , 37 ]. The questions of family-medicine, elder-care, and rural-health physicians have been explored [ 25 , 29 , 30 , 32 , 34 , 44 ]. Experiments have been done on different ways of capturing clinical questions through voice and other input media [ 28 , 39 – 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other taxonomies may better capture the nature of questions people naturally ask, for example a linguistic taxonomy of the type described here. Access to EBM resources is greatly facilitated by framing enquiries in the language of EBM [ 9 , 10 ]. People do not naturally do this.…”
Section: Discussionmentioning
confidence: 99%